Improved Electrochemical Performance of 0.5Li2MnO3·0.5LiNi0.5Mn0.5O2 Cathode Materials for Lithium Ion Batteries Synthesized by Ionic-Liquid-Assisted Hydrothermal Method - Xiang, Yanhong; Jiang, Youliang; Liu, Saiqiu; Wu, Jianhua; Liu, Zhixiong; Zhu, Ling; Xiong, Lizhi; He, Zeqiang; Wu, Xianwen (Frontiers in Chemistry, 2020)
Well-dispersed Li-rich Mn-based 0.5Li2MnO3•0.5LiNi0.5Mn0.5O2 nanoparticles with diameter ranging from 50 to 100 nm are synthesized by a hydrothermal method in the presence of N-hexyl pyridinium tetrafluoroborate ionic liquid ([HPy][BF4]). The microstructures and electrochemical performance of the prepared cathode materials are characterized by XRD, SEM, TEM and electrochemical measurements. The XRD results show that the sample prepared by ionic liquid assisted hydrothermal method exhibits a typical Li-rich Mn-based pure phase and lower cation mixing. SEM and TEM images indicate that the extent of particle agglomeration of the ionic liquid assisted sample is lower compared to the traditional hydrothermal sample. Electrochemical test results indicate that the materials synthesized by ionic liquid assisted hydrothermal method exhibit better rate capability and cyclability. Besides, EIS results suggest that the charge transfer resistance of 0.5Li2MnO3•0.5LiNi0.5Mn0.5O2 synthesized by ionic liquid assisted hydrothermal method is much lower, which enhances the reaction kinetics.